Hubert, Rosario. 2023. Disoriented Disciplines: China, Latin America, and the Shape of World Literature. Evanston, Illinois: Northwestern University Press. 324 pp. - Martina Altalef; Telma Carvalho (Compendium)
Book review of Disoriented Disciplines: China, Latin America, and the Shape of World Literature (2023), by Rosario Hubert, exploring the transnational, diasporic and global dimensions of cultural manifestations of China in Latin America.